ENSURING JOB STABILITY: PROBLEMS AND PROSPECTS (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This article analyzes the issues of ensuring job stability. Based on survey results, the impact of employers on employment and the challenges they face are examined. Conclusions and recommendations necessary for ensuring job stability have been developed.
Keywords: job position, stable employment, job provision, labor market, employers